Priming and performance rating accuracy: notification of rating purpose and exposure to comparative evaluation strategies - Waples, Christopher J. (Kansas State University, 2013)
Despite the functional importance of performance appraisals in organizational settings, rating inaccuracies persist and have been a widely researched topic for decades. Contemporary efforts to explore the problem have turned to components of accuracy to foster a more detailed understanding of the influence of situational factors and individual biases. In particular, a great deal of research has examined the role of rating purpose (e.g., administrative, developmental) on subsequent accuracy, consistently revealing greater leniency for administrative ratings than for developmental ratings. On the basis of spreading activation theory, rating purpose was conceptualized as a priming event, and in combination with rating strategy priming, was expected to prompt predictable enhancements to specific components of accuracy. Participants for this experimental study were 160 undergraduate students. Participants were randomly assigned a rating purpose with “real-world” implications, and exposed to a strategy priming task designed to promote specific rating cognitions. Students viewed video-recorded competitive marching band performances, and rated them. Participants’ ratings were compared to those made by experienced raters to compute accuracy estimates. Results were largely non-significant, but in the directions expected. Limitations and future research opportunities are discussed.
Keywords: Performance Appraisal; Rating Accuracy; Priming - Application; Rating Purpose; Psychology (0621)